Kinesthetic and vestibular information modulate alpha activity during spatial navigation: a mobile EEG study - Ehinger, Benedikt V.; Fischer, Petra; Gert, Anna L.; Kaufhold, Lilli; Weber, Felix; Pipa, Gordon; König, Peter (Frontiers in Human Neuroscience, 2014)
In everyday life, spatial navigation involving locomotion provides congruent visual, vestibular and kinesthetic information that need to be integrated. Yet, previous studies on human brain activity during navigation focus on stationary setups, neglecting vestibular and kinesthetic feedback. The aim of our work is to uncover the influence of those sensory modalities on cortical processing. We developed a fully immersive virtual reality setup combined with high-density mobile electroencephalography (EEG). Participants traversed one leg of a triangle, turned on the spot, continued along the second leg and finally indicated the location of their starting position. Vestibular and kinesthetic information was provided either in combination, as isolated sources of information or not at all within a 2x2 full factorial intra-subjects design. EEG data were processed by clustering independent components, and time-frequency spectrograms were calculated. In parietal, occipital and temporal clusters, we detected alpha suppression during the turning movement, which is associated with a heightened demand of visuo-attentional processing, and closely resembles results reported in previous stationary studies. This decrease is present in all conditions and therefore seems to generalize to more natural settings. Yet, in incongruent conditions, when different sensory modalities did not match, the decrease is significantly stronger. Additionally, in more anterior areas, we found that providing only vestibular but no kinesthetic information results in alpha increase. These observations demonstrate that stationary experiments omit important aspects of sensory feedback. Therefore, it is important to develop more natural experimental settings in order to capture a more complete picture of neural correlates of spatial navigation.